An exploration of suicidal ideation and attempts, and care use and unmet need among suicide-ideators in a Belgian population study - Eva Rens; Gwendolyn Portzky; Manuel Morrens; Geert Dom; Kris Van den Broeck; Mandy Gijzen (BMC Public Health, 2023)
Abstract Background Suicidal ideation, or thinking about death and suicide, is common across all layers of society. The aim of this paper is to add to the understanding of suicidal ideation in the general population, as well as help-seeking behaviors and perceived unmet mental health needs among those who report suicidal thoughts. Methods The research is part of a representative population-based survey study of mental wellbeing in Antwerp (Flanders, Belgium) carried out in 2021. A total of 1202 participants between 15 and 80 years old answered the Ask Suicide-Screening Questions (ASQ), and an additional question about suicide plans. Participation was by invitation only and possible online or via a postal paper questionnaire. Univariate and multivariate logistic regression analyses were used to explore the association between both current suicidal ideation and self-reported lifetime suicide attempt with the sociodemographic factors age, gender, educational level, origin and financial distress. Moreover, formal care use for mental health was examined among those experiencing suicidal ideation, and logistic regression analyses were used to assess associated sociodemographic factors. Finally, perceived unmet mental health needs were assessed among suicide ideators. Results The point-prevalence of suicidal ideation was 8.6% and was higher among younger age groups and individuals reporting financial distress. The lifetime-prevalence of suicide attempts is 6.5% and was higher in younger people and individuals with a primary educational level and with financial distress. About half (45.6%) of those with suicidal ideation consulted a professional for mental health problems in the past twelve months. Men and those with a primary educational level were less likely to seek help. Half of suicide ideators without care use perceived some need for mental health care, and a third of suicide ideators who used care perceived the obtained help as insufficient, resulting in a population prevalence of 3.6% suicide ideators with a fully or partially perceived unmet need. Conclusions The prevalence of suicide attempts, suicidal ideation and unmet needs among suicide-ideators is high in this Belgian sample. Mental health care need perception in suicide ideators needs further investigation.